2019
DOI: 10.1016/j.neuroimage.2018.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and comparative evaluation of nonlinear deformation algorithms for atlas-based segmentation of DBS target nuclei

Abstract: Nonlinear registration of individual brain MRI scans to standard brain templates is common practice in neuroimaging and multiple registration algorithms have been developed and refined over the last 20 years. However, little has been done to quantitatively compare the available algorithms and much of that work has exclusively focused on cortical structures given their importance in the fMRI literature. In contrast, for clinical applications such as functional neurosurgery and deep brain stimulation (DBS), prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 121 publications
(169 citation statements)
references
References 63 publications
6
158
2
Order By: Relevance
“…To minimize this issue, we used a modern neuroimaging pipeline that has been scientifically validated in numerous studies and involved advanced concepts such as brain shift correction 83 , multispectral normalization, subcortical refinement 83 and phantom-validated electrode localizations 84 . The normalization strategy that was applied was found to automatically segment the STN as precisely as manual expert segmentations 85 and each step of the pipeline was carefully assessed and corrected if needed by a team with long-standing expertise in this area 86,87 . Besides, both post-operative CT (thirty-three patients) and post-operative MRI (seven-teen patients) were used for electrode localization in the current dataset.…”
Section: Limitationsmentioning
confidence: 99%
“…To minimize this issue, we used a modern neuroimaging pipeline that has been scientifically validated in numerous studies and involved advanced concepts such as brain shift correction 83 , multispectral normalization, subcortical refinement 83 and phantom-validated electrode localizations 84 . The normalization strategy that was applied was found to automatically segment the STN as precisely as manual expert segmentations 85 and each step of the pipeline was carefully assessed and corrected if needed by a team with long-standing expertise in this area 86,87 . Besides, both post-operative CT (thirty-three patients) and post-operative MRI (seven-teen patients) were used for electrode localization in the current dataset.…”
Section: Limitationsmentioning
confidence: 99%
“…The focal template misregistrations we have identified in fMRIPrep with AFIDs are meant to serve as a baseline for refinement in future versions that can be compared transparently and potentially incorporated for testing new versions as part of a continuous integration workflow. Using additional image contrasts (Xiao et al, 2017) or subcortical tissue priors (Ewert et al, 2019) to drive template registration have been demonstrated using conventional voxel overlap techniques to result in more optimal registrations that can also be tested using the AFIDs framework.…”
Section: Subject-to-template Registrationmentioning
confidence: 99%
“…In some patients where this strategy failed, a multispectral implementation of the Unified Segmentation approach implemented in Statistical Parametric Mapping software (SPM12;http://www.fil.ion.ucl.ac.uk/spm) was applied. These two methods are available as pre-sets in Lead-DBS and were top-performers to segment the STN with precision comparable to manual expert segmentations in a recent comparative study 22 . DBS contacts were automatically pre-reconstructed using PaCER or the TRAC/CORE approach and manually refined if needed 20 .…”
Section: Localization Of Dbs Electrodesmentioning
confidence: 99%